2013
DOI: 10.3389/fmicb.2013.00359
|View full text |Cite
|
Sign up to set email alerts
|

Methanogens at the top of the world: occurrence and potential activity of methanogens in newly deglaciated soils in high-altitude cold deserts in the Western Himalayas

Abstract: Methanogens typically occur in reduced anoxic environments. However, in recent studies it has been shown that many aerated upland soils, including desert soils also host active methanogens. Here we show that soil samples from high-altitude cold deserts in the western Himalayas (Ladakh, India) produce CH4 after incubation as slurry under anoxic conditions at rates comparable to those of hot desert soils. Samples of matured soil from three different vegetation belts (arid, steppe, and subnival) were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 66 publications
1
24
2
Order By: Relevance
“…Methanocellales appears to have exceptional aero‐tolerant abilities, and all three strains encode a substantial number of genes involved in antioxidant resistance (Erkel et al ., ; Angel et al ., 2011; 2012; Sakai et al ., ; Yuan et al ., ; Lü and Lu, ; Aschenbach et al ., ). However, a robust antioxidant system would also need a strong energy source that is oxygen tolerant, as many reactions consume reducing equivalents (Imlay, ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Methanocellales appears to have exceptional aero‐tolerant abilities, and all three strains encode a substantial number of genes involved in antioxidant resistance (Erkel et al ., ; Angel et al ., 2011; 2012; Sakai et al ., ; Yuan et al ., ; Lü and Lu, ; Aschenbach et al ., ). However, a robust antioxidant system would also need a strong energy source that is oxygen tolerant, as many reactions consume reducing equivalents (Imlay, ).…”
Section: Resultsmentioning
confidence: 97%
“…For example, Methanocellales and Class II methanogens are commonly found to be active in rice soil and wetland where low H 2 concentrations of 1–10 pa prevail (Conrad et al ., ; Liu and Whitman, ; Thauer et al ., ). Methanocellales also shares some unique habitats with Class III methanogens, such as upland soils where aeration and desiccation are common, although methanogens typically occur in reduced anoxic and moisturized environments (Angel et al ., 2011; 2012; Aschenbach et al ., ). Genome sequences for M. arvoryzae , M. paludicola and M. conradii have begun to elucidate basic features of the Methanocellales ' lifestyle, which include hydrogenotrophic methanogenesis and aerotolerance (Erkel et al ., ; Sakai et al ., ; Lü and Lu, ).…”
Section: Introductionmentioning
confidence: 97%
“…and Methanocella spp. are conspicuous residents of dry and aerated soils, even in desert biological soil crusts (Nicol et al ., ; Poplawski et al ., ; Angel et al ., ; Conrad et al ., ; Aschenbach et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that these microorganisms are also able to grow in aerated places like deserts soils (Aśchenbach et al, 2013). Annually, approximately 600 million metric tons of methane is produced.…”
Section: Methanogenesis and Methanogensmentioning
confidence: 99%